Concentration Of Calcium Acceptor Injective Depomedroxion Of Acetate Progesteron With Combination Of Perimenopause Women - Risnawati; Nasruddin; Werna Nontji (Jurnal Life Birth, 2020)
Contraception injection is used by different age groups, both 3 months (progestin-only)as well as 1 month (combination). The research aimed to investigate the differences in the calcium concentration between the acceptors of the depomedroxion progesterone acetate injection and the acceptors of the combination injection in a woman with perimenopause. The research used the cross-sectional method, and the samples comprise 32 women who were chosen using the accidental sampling technique. The data were analyzed statistically using the chi-square method. The research results indicate that the majority of respondents aged between 40-45 years, multiparity, have long used contraception > 24 months, Nutritional status (BMI) normal. The Research result indicates that there is a relationship between long use depomedroxion progesterone acetate injection contraception and the calcium concentration (r=0.006). The Research result indicated that there was a difference in the calcium concentration between the acceptors of the injection of acetate progesterone depomedroxion and the acceptors of the combination Injection in women with perimenopause (r=0.006). It suggested routine inspection of calcium concentration a minimum of 2 years.